2021
DOI: 10.1021/jacs.0c10704
|View full text |Cite
|
Sign up to set email alerts
|

Delocalized Metal–Oxygen π-Redox Is the Origin of Anomalous Nonhysteretic Capacity in Li-Ion and Na-Ion Cathode Materials

Abstract: The anomalous capacity of Li-excess cathode materials has ignited a vigorous debate over the nature of the underlying redox mechanism, which promises to substantially increase the energy density of rechargeable batteries. Unfortunately, nearly all materials exhibiting this anomalous capacity suffer from irreversible structural changes and voltage hysteresis. Non-hysteretic excess capacity has been demonstrated in Na 2 Mn 3 O 7 and Li 2 IrO 3 , making these materials key to understanding the electronic, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 55 publications
(156 reference statements)
4
118
0
Order By: Relevance
“…The existence of thermodynamically favorable O −• over the peroxide-like O 2 2− dimers was predicted by computations and showed that hole stabilization occurred through a (σ + π) multiorbital Mn-O bond. Similar predictions were reported in the work of Kitchaev et al, where a π-bonded Mn-d and O-p orbital network formed a collective deloca-lized redox center [81]. Therefore, the authors concluded that such a π-network rather than any local bonding environment was responsible for the two-step voltage profile with a lowvoltage hysteresis and structural evolution observed in Na 2 Mn 3 O 7 .…”
Section: P3-type Layered Compounds Na X [A Y Mnsupporting
confidence: 85%
See 2 more Smart Citations
“…The existence of thermodynamically favorable O −• over the peroxide-like O 2 2− dimers was predicted by computations and showed that hole stabilization occurred through a (σ + π) multiorbital Mn-O bond. Similar predictions were reported in the work of Kitchaev et al, where a π-bonded Mn-d and O-p orbital network formed a collective deloca-lized redox center [81]. Therefore, the authors concluded that such a π-network rather than any local bonding environment was responsible for the two-step voltage profile with a lowvoltage hysteresis and structural evolution observed in Na 2 Mn 3 O 7 .…”
Section: P3-type Layered Compounds Na X [A Y Mnsupporting
confidence: 85%
“…However, the overall stacking sequence of oxygen ions was barely changed during both steps of Na extraction/insertion, which differs from the behavior in P2/P3 cathodes, where extraction/insertion of Na lead to the formation of O-P phases with simultaneous decrease of the interlayer distance. [81]. Therefore, the authors concluded that such a π-network rather than any local bonding environment was responsible for the two-step voltage profile with a lowvoltage hysteresis and structural evolution observed in Na 2 Mn 3 O 7 .…”
Section: Sodium-deficient Layered Structuresmentioning
confidence: 95%
See 1 more Smart Citation
“…43 ) phases. Apparently, in such ribbon or mesh superstructures, oxygen redox could proceed by involving O 2p localized holes or delocalized π states 44 that are free of the reductive coupling process, like those having redox from 'TM-O' bonding states (for example LiCoO 2 (ref. 1 ) and Na x [Ni 1/3 Mn 2/3 ]O 2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, [22] a possible strategy to suppress the voltage hysteresis in O-redox cathodes is to prevent O 2 formation by inhibiting TM migration; i.e., kinetically trapping the charged structures in a metastable state with bulk localised, 'split-polaron' or delocalised Oholes. [16,58,66] We suggest that this strategy is unlikely to be effective in Li 2 MnO 2 F because of relatively easy Mn migration. This is a two-fold effect, related to the high Li:TM ratio in Li 2 MnO 2 F. Firstly, a high concentration of Li will simply allow many possible vacant cation sites for Mn to migrate into on Li extraction.…”
Section: Discussion: Strategies To Harness Reversible O-redoxmentioning
confidence: 94%